2022
DOI: 10.1186/s12885-022-09212-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholinesterase may independently predict prognosis in non-small-cell lung cancer

Abstract: Background Serum cholinesterase (ChE) was found to be involved in cancer initiation and progression. However, the survival association between serum ChE and non-small cell lung cancer (NSCLC) has not been extensively discussed. In the present study, we aim to elevate the role of ChE in overall survival (OS) of NSCLC patients. Methods A total of 961 histologically confirmed NSCLC patients diagnosed between 2013 and 2018 in a provincial cancer hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Patients with malignancy often receive high-dose chemotherapy, experience weight loss and exhibit malnutrition, which can affect liver synthetic function, including CHE production. Serum CHE has been reported to be a prognostic factor in several solid cancers [8,12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with malignancy often receive high-dose chemotherapy, experience weight loss and exhibit malnutrition, which can affect liver synthetic function, including CHE production. Serum CHE has been reported to be a prognostic factor in several solid cancers [8,12] .…”
Section: Discussionmentioning
confidence: 99%
“…Serum cholinesterase (CHE), as a reliable indicator of liver synthetic function, is closely linked to conditions such as hepatic impairment, malnutrition, heart failure, and progressive systemic in ammation [7] . Recent studies have shown that low serum CHE levels are associated with poor prognosis and decreased chemotherapy effectiveness in various solid cancers, such as gastric cancer [8] , prostate cancer [9] , pancreatic cancer [10] , colorectal cancer [11] , and non-small cell lung cancer [12] , regardless of hepatic involvement.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year survival rate for lung cancer patients is approximately 4-17%, depending on the stage and region [24]. Considering the different subtypes of lung cancer, targeted therapy is also increasingly used in the personalized treatment of patients [25]. Based on a large number of studies, established risk factors for NSCLC may affect the expression levels of lncRNA in NSCLC tissues and cell lines, thereby affecting the occurrence, development and other malignant phenotypes of NSCLC [25].…”
Section: Discussionmentioning
confidence: 99%
“…Serum cholinesterase level was significantly lower in the GC group than in the benign gastric disease group [143]. Also, NSCLC patients with a higher level of serum cholinesterase were observed a better prognosis in survival [286]. Its precursor polypeptide chain has 602 AA, where AA 1-28 -the signal peptide and AA 29-602 -cholinesterase (pI/Mw: 6.33/65084).…”
Section: Cholinesterase (Chle_human)mentioning
confidence: 99%